Spending with unnecessary complementary tests for hypertension and diabetes in health services - Thiago Roberto Castellane Arena; Marli de Carvalho Jericó; Liliana Cristina de Castro; Valéria Castilho; Antonio Fernandes Costa Lima
The aims of this study were to analyze unnecessary laboratory exams for patients with hypertension and diabetes and to check the expenditures involved. This is an exploratory-descriptive, cross-sectional study with a quantitative approach. We used data from medical records of 293 patients registered in primary units - the Family Health Center (NSF3); secondary: School Health Center (CSE); and tertiary: Hospital das Clínicas (HC) from 2006 to 2009 in a city in Southeastern Brazil. We identified a total of 9,522 laboratory tests, of which 5.97% were unnecessary. Of these, about 58% were requested by NSF3 and 42% by CSE. Results suggest there is a lack of integration among different levels of health care, which result in misallocation of resources and unnecessary spending.